2020
DOI: 10.7717/peerj.8878
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors ofHelicobacter pyloriinfection among children in Kuichong Subdistrict of Shenzhen City, China

Abstract: Background Helicobacter pylori infection is a significant burden to the public health in China as it can lead to various gastric diseases including peptic ulcers and gastric cancer. Since most infections occurred during childhood, it is therefore necessary to understand the prevalence and risk determinants of this bacterial infection in children. Herewith, we conducted a cross-sectional study in the Kuichong Subdistrict of Shenzhen City to assess the prevalence and risk factors of H. pylori infection among chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…This inverse association was also comparable to a study of Nguyet et al conducted in the North of Vietnam, which indicated low parental education as a risk factor of acquiring H. pylori [ 22 ]. This finding was also consistent with other reports from China [ 23 ], Pakistan [ 24 ], Iran [ 25 ] which also pointed that children whose parents had a lower education level were significantly at a higher risk of H. pylori infection. In addition, our study found that pupils with parents who completed only primary school had a higher prevalence than those with parents who completed a higher educational degree.…”
Section: Discussionsupporting
confidence: 92%
“…This inverse association was also comparable to a study of Nguyet et al conducted in the North of Vietnam, which indicated low parental education as a risk factor of acquiring H. pylori [ 22 ]. This finding was also consistent with other reports from China [ 23 ], Pakistan [ 24 ], Iran [ 25 ] which also pointed that children whose parents had a lower education level were significantly at a higher risk of H. pylori infection. In addition, our study found that pupils with parents who completed only primary school had a higher prevalence than those with parents who completed a higher educational degree.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, families with low education levels, rural residence, and low incomes often lack sufficient health knowledge, pay less attention to children's illnesses, and maintain relatively poor hygiene standards. Most of these families share tableware during meals, which are major contributors to the recurrence of H. pylori infection (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Varios estudios demuestran que la primoinfección se adquiere durante la primera infancia y la principal forma de transmisión ocurre de persona a persona en el entorno intrafamiliar (39)(40)(41)(42)(43)(44)(45)(46) . Por tanto, son necesarias nuevas investigaciones en la población pediátrica en Antioquia para comparar los hallazgos obtenidos con otros estudios en infantes, porque no se descarta que la infección la hayan adquirido en su niñez o adolescencia, situación común en países en desarrollo como Colombia (47)(48)(49) .…”
Section: Diagnóstico De H Pylori Y Factores Asociados Con Infecciónunclassified